Use of Paclitaxel-Coated Balloon Catheter Dilation to Reduce In-Stent Restenosis in Transjugular Intrahepatic Portosystemic Shunt (TIPS) - Marticorena Garcia, S. R.; Langmann, M.; Schnorr, B.; Günther, R. W.; Hamm, B.; Althoff, C. E. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: Paclitaxel-coated balloons (PCB) inhibit neointimal proliferation in arteries. The purpose of this retrospective analysis was to investigate the effect of PCB in in-stent restenosis after transjugular intrahepatic portosystemic shunt (TIPS) in patients with cirrhotic liver disease.Materials and Methods: Six patients (mean age: 65 ± 10 years) with recurrent in-stent restenoses in TIPS (5 bare stents, 1 covered stent) underwent a single percutaneous transluminal angioplasty (PTA) with PCB (3 µg paclitaxel/mm2). Post-interventional outcome and patency were compared with those of prior plain optimal balloon angioplasty (POBA) in the same patients. During a two-year follow-up period, all patients underwent angiographic examinations at 6-month intervals. In-stent minimal lumen diameter (MLD) and late lumen loss (LLL) were assessed. Paclitaxel residues on balloon and sheath surfaces as well as venous plasma concentrations (0 – 24 hours) were analyzed.Results: PCB decreased the need for clinically driven repeat PTA (POBA: 53 % of angiographic examinations; paclitaxel PTA: 19 %; P = 0.014). LLL/diameter stenosis was higher after POBA (2.4 ± 1.5 mm/28 ± 18 %) than after PCB (0.5 ± 0.8 mm/7 ± 11 %, P = 0.029). Residual paclitaxel on balloons was 28 ± 9 % of dose and 0.2 ± 0.1 % on sheath surfaces. Paclitaxel plasma concentrations were below detectable levels throughout the first 24 hours after the interventions in all patients. The procedure was well tolerated and no clinical side effects attributable to paclitaxel were observed.Conclusion: In patients with recurrent in-stent stenoses, a single PTA with PCB resulted in a prolonged secondary patency due to pseudointimahyperplasia without a systemic effect of paclitaxel.Key points:• Intimahyperplasia is a common reason for long-time TIPS dysfunction• First-in-man local paclitaxel application in TIPS patients with recurrent in-stent stenoses• PTA with PCB resulted in a prolonged secondary patency compared to POBA• No systemic effects of Paclitaxel were detectedCitation Format:• Marticorena Garcia SR, Langmann M, Schnorr B et al. Use of Paclitaxel-Coated Balloon Catheter Dilation to Reduce In-Stent Restenosis in Transjugular Intrahepatic Portosystemic Shunt (TIPS). Fortschr Röntgenstr 2016; 188: 374 – 380
Keywords: portosystemic shunt; transjugular intrahepatic balloon angioplasty; paclitaxel